2006
DOI: 10.1177/107602960601200104
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulopathy in Stroke Patients with Nonvalvular Atrial Fibrillation: Hematologic and Cardiologic Investigations

Abstract: The coagulation system is activated and coagulation activation markers are elevated in acute ischemic stroke with nonvalvular atrial fibrillation (NVAF). The etiology, severity, and prognosis of the ischemic stroke might be estimated with the level of the activation of the coagulation system. In this study, prothrombin F1+2 (F1+2), D-dimer, and fibrinogen levels were measured in patients with acute ischemic stroke with and without NVAF, and stroke severity was compared with these hemostatic parameters. Of 55 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…Increases in prothrombin fragment and thrombin-antithrombin complexes have been observed in patients with AF-related strokes 191 and in those with transesophageal spontaneous echo contrast. 192 Other hemostatic factors have been implicated in contributing to the hypercoagulable state including fibrinogen, D-dimer, factor VIII, and von Willebrand factor.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in prothrombin fragment and thrombin-antithrombin complexes have been observed in patients with AF-related strokes 191 and in those with transesophageal spontaneous echo contrast. 192 Other hemostatic factors have been implicated in contributing to the hypercoagulable state including fibrinogen, D-dimer, factor VIII, and von Willebrand factor.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…192 Other hemostatic factors have been implicated in contributing to the hypercoagulable state including fibrinogen, D-dimer, factor VIII, and von Willebrand factor. 191, 193–196 However, in an adjusted model, the FHS showed that such abnormalities are ascribed to AF RFs and presence of cardiovascular disease rather than AF alone. 197 Finally, inflammation may mediate endothelial dysfunction and hypercoagulability.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This conclusion is disputed by others. 17 In our patients with elevated D-dimer levels, none of them had atrial fibrillation. However, high-grade carotid stenosis (≥75%) or carotid occlusion was found in five of our patients with elevated D-dimer levels.…”
Section: Discussionmentioning
confidence: 54%
“…In fact, AF is often characterized by endocardial damage, from dilatation of the atria, 7 blood slowdown and stasis, 8 related to the anatomy of the atria, and abnormal changes in blood constituents, including platelet activation, 9 as well as inflammation 10 and changes in growth factor. 11 For these reasons, AF can favor a prothrombotic and hypercoagulable state.…”
mentioning
confidence: 99%